ESR STUDIES OF SUPERCONDUCTING CUPRATES - LOW MAGNETIC-FIELD EFFECTS AT X-BAND AND 300 MHZ - Janes, R; Edwards, P; Liu, R; Stevens, A; Symons, M (Springer India, 1991)
Low field microwave absorption in cuprate superconductors below T c is reported in a range of materials using ESR spectrometers operating at X-band and 300 MHz. The radiofrequency apparatus facilitated a detailed study of the 0-100G region where the absorption is most intense and we include here a brief discussion of the effects of incident microwave power and sample temperature on the intensity and position of the signal. © 1991 Indian Academy of Sciences.